Law, society, and corruption lessons from the Central Asian context - Urinboyev, Rustamjon; Svensson, Måns 1969- (Abingdon, Oxon Routledge, 2025)
This book presents new socio-legal perspectives and insights on the social life of corruption and anti-corruption in authoritarian regimes. This book takes up the case of Uzbekistan-an authoritarian regime in Central Asia and one of the most corrupt countries in the world according to Transparency International's Corruption Perceptions Index-and examines the corruption that developed in a tightly closed authoritarian regime permeated by a large-scale shadow economy, a weak rule of law, and a collectivist legal culture. Building on socio-legal frameworks of legal compliance, living law and legal pluralism, the central argument of the book is that the roles, meanings, and logics of corruption are fluid, and depend on a myriad of structural variables, and contextual and situational factors. This book will be of value to researchers, academics and students in the fields of sociology of law, legal anthropology and Central Asian studies, especially those with an interest on the intersection of law, society and corruption in authoritarian regime contexts"--
Understanding corruption in authoritarian regimes--Political environment and governance trajectories in Uzbekistan--Anticorruption laws, policies, and initiatives in Uzbekistan : an overview of the legal and institutional environment--Law, society, and corruption in Uzbekistan : a socio-legal analysis of macro-level developments --Corruption, informality, and coping strategies in meso-level arenas--The social life of corruption in micro-level arenas--The interplay between law, society, and (anti-) corruption in authoritarian regimes.
Includes bibliographical references and index.
Keywords: Authoritarianism -- Asia, Central; Authoritarianism -- Uzbekistan; Misconduct in office -- Law and legislation -- Asia, Central; Misconduct in office -- Law and legislation -- Uzbekistan; Political corruption -- Law and legislation -- Asia, Central; Political corruption -- Law and legislation -- Uzbekistan